Collective effects of multiple chiral selectors on enantioselective adsorption - Bao, Xiaoying (Langmuir : the ACS journal of surfaces and colloids, 2009)
Molecular simulations were performed to predict the adsorption of racemic mixtures of (R,S)-1,3-dimethylallene (DMA) in three homochiral metal-organic frameworks (HMOFs). All three HMOFs include the same chiral linker, (R)-6,6'-dichloro-2,2'-dihydroxy-1,1'-binaphthyl-4,4'-bipyridine (L), but have different topologies. While a single linker L shows very little enantioselectivity between the DMA enantiomers, the three HMOFs with closely packed linkers L have enantiomeric excesses of 6%, 28%, and 45%, showing that closely situated chiral selectors function synergistically to enhance the enantioselectivity. Both the confinement created by the linkers and the number of chiral linkers that form the confinement are important in enhancing the enantioselectivity. In addition, the simulations show that the enantioselectivity of the three HMOFs may be further enhanced by modifying the composition of the linker L